Upcoming SlideShare
×

# Multiplying polynomials

2,756 views

Published on

Published in: Education
0 Likes
Statistics
Notes
• Full Name
Comment goes here.

Are you sure you want to Yes No
• Be the first to comment

• Be the first to like this

Views
Total views
2,756
On SlideShare
0
From Embeds
0
Number of Embeds
2,036
Actions
Shares
0
29
0
Likes
0
Embeds 0
No embeds

No notes for slide

### Multiplying polynomials

1. 1. Multiplying Polynomials<br />NCVPS <br />Summer 2010 <br />
2. 2. Multiplying two terms<br />Use the product rule to combine exponents:<br />x2x3 = x(2 + 3) = x5<br /> a(2a5) = 2a(1+5) = 2a6<br /> 3x2(2x5) = 3*2x(2+ 5) = 6x7<br />Do you see in this last example that the coefficients are multiplied together?<br />
3. 3. Multiplying a Monomial with a Binomial<br />A monomial is a single term, such as 2x<br />A binomial means there are two terms in the expression. An example is 3x + 1.<br />Let’s multiply: <br /> 2x(3x + 1) <br />= 2x(3x) + 2x (1) using distributive property<br />= 6x2 + 2x<br />
4. 4. You Try One!<br />Example 2: 4x(x – 3)<br />Click on the slide when ready to move forward!<br />
5. 5. You Try One!<br />Example 2: 4x(x – 3)<br /> 4x(x – 3)<br />= 4x(x) + 4x(-3)<br />= 4x2 + (-12x) <br />= 4x2 – 12x<br />
6. 6. Two Binomials Multiplied<br />Let’s look at (2x – 3)(x + 4).<br />Each term in the first binomial is distributed against the second binomial.<br /> 2x(x+4) + (-3)(x + 4)<br />= 2x(x) + 2x(4) + (-3)(x) + (-3)(4)<br />= 2x2 + 8x + (-3x) + (-12)<br />= 2x2 + 5x - 12<br />
7. 7. You Try One!<br />Multiply (5x - 1)(2x + 3). Click on the slide when you are ready!<br />
8. 8. You Try One!<br />Multiply: (5x - 1)(2x + 3)<br />=(5x)(2x + 3) + (-1)(2x + 3)<br />=(5x)(2x) +5x(3) + (-1)(2x) + (-1)(3)<br />=10x2 + 15x – 2x – 3<br />=10x2 + 13x - 3<br />
9. 9. Are you ready? <br />See your teacher if you have further questions!<br />Take your formative assessment!<br />